SWOT Analysis of Community-based Tourism Performance in Akwa Ibom State as a Tool for Sustainable Tourism Development in the 21st Century - Nsisong Christopher Ekong; Augustine Michael Imikan (RIRAI Publisher, 2022)
The study sought to analyzed community-based tourism performance and introduces it as a tool for sustainable tourism development in Akwa Ibom. The study was descriptive in nature and adopted purposive sampling method to select two communities in each of the senatorial district making a sample size of six for the study. Data were obtained through questionnaire forms, interviews and personal observations. The questionnaire forms were administered to a total of three hundred (300) respondents using simple random sampling method. SWOT analysis technique was adopted as the analytical tool for the study. The result shows significantly that community-based tourism performance has impact on the locals and the tourism communities which also serves as an avenue for sustainable tourism development. Also, the involvement of the locals in decision-making gives them chances to develop and build confidence in the tourism industry. Therefore, the researcher recommends that the local communities should involve and participate immensely in community-based tourism related activities in Akwa Ibom State and they should be integrated in decision-making, planning and management.